Antibodies to biotinylated red blood cells in adults and infants: improved detection, partial characterization, and dependence on red blood cell‐biotin dose. Issue 6 (5th March 2017) - Schmidt, Robert L.; Mock, Donald M.; Franco, Robert S.; Cohen, Robert M.; North, Anne K.; Cancelas, José A.; Geisen, Christof; Strauss, Ronald G.; Vlaar, Alexander P.; Nalbant, Demet; Widness, John A.
Abstract : BACKGROUND: Biotin‐labeled red blood cells (BioRBCs) are used for in vivo kinetic studies. Because BioRBC dosing occasionally induces antibodies, a sensitive and specific anti‐BioRBC detection assay is needed. STUDY DESIGN AND METHODS: Aims were to 1) develop a gel card assay to evaluate existing, naturally occurring and BioRBC‐induced plasma antibodies, 2) compare gel card and tube agglutination detection results, and 3) test for a relationship of antibody induction and BioRBC dose. Reagent BioRBCs were prepared using sulfo‐NHS biotin ranging from densities 18 (BioRBC‐18) to 1458 (BioRBC‐1458) µg/mL RBCs. RESULTS: Among BioRBC‐exposed subjects, gel card and tube agglutination results were concordant in 21 of 22 adults and all 19 infant plasma samples. Gel card antibody detection sensitivity was more than 10‐fold greater than tube agglutination. Twelve to 16 weeks after BioRBC exposure, induced anti‐antibodies were detected by gel card in three of 26 adults (12%) at reagent densities BioRBC‐256 or less, but in none of 41 infants. Importantly, induced anti‐BioRBC antibodies were associated with higher BioRBC dose (p  =  0.008); no antibodies were detected in 18 subjects who received BioRBC doses less than or equal to BioRBC‐18. For noninduced BioRBC antibodies, six of 1125 naïve adults (0.3%) and none of 46 naïve infants demonstrated existing anti‐BioRBC antibodies using reagent BioRBC‐140 or ‐162. Existing anti‐BioRBCs were all neutralized by biotin compounds, while induced antibodies were not. CONCLUSIONS: The gel card assay is more sensitive than the tube agglutination assay. We recommend reagent BioRBC‐256 for identifying anti‐BioRBCs. Use of a low total RBC biotin label dose (≤ BioRBC‐18) may minimize antibody induction.